PERTANGGUNGJAWABAN PIDANA KORPORASI MENGEDARKAN MAKANAN OLAHAN TANPA IZIN EDAR - Kartina Pakpahan; Leviyanti Leviyanti; Heni Widiyaani; Ferris Chandra (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
The role of the state is important in realizing the availability regulation for the fulfillment of safe, quality, nutritious food. This study aims to find out the positive law regarding criminal liability to perpetrators who circulate food without permission and crime prevention efforts. Using library research, normative juridical methods, analyzing qualitative approach data. Packaged, circulated food must have a marketing authorization. Corporations may be liable to include organs from corporations if they have errors as regulated in Article 91. The act of distributing certain processed domestic and foreign processed food products that are marketed in secure packaging without permission with a criminal fine is regulated in Article 142 of the Food Law. Mitigation efforts are carried out through both penal and non-penal policies. Keywords: criminal liability, corporation, food without permission